Prinsip-Prinsip Pemberdayaan Masyarakat Demi Mengentaskan Kemiskinan dalam Perspektif Islam - Furqon, Mochammad Busyro Nurul; Aliyah, Nelud Darojaatul (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Poverty is an issue that needs to be resolved because it is becoming a problem for every nation and culture. It is also considered a disease in Islam that has to be healed. Community empowerment is one of the most successful strategies for reducing poverty. In order to control the environment, accomplish personal objectives, cooperate together, and support one another in maximizing their quality of life, communities, groups, and people employ community empowerment techniques. Numerous verses in the Qur'an discuss the idea of collective empowerment. This essay uses thematic interpretation techniques to examine community empowerment from a Qur'anic perspective. The ukhuwwah, ta'awun, and equality principles are the cornerstones of communal empowerment found in the Qur'an. According to the Qur'an, the phases of empowerment include ongoing self-improvement, supporting zakat and infaq initiatives, providing community training and skills education, and abstaining from economic practices that are forbidden by Islam, such as monopoly and hoarding (ihtikar).